2008
DOI: 10.1007/s11332-008-0046-6
|View full text |Cite
|
Sign up to set email alerts
|

Maximal oxygen consumption and energy cost of running after a long-lasting running race: the 100 km of Sahara

Abstract: The purpose of this study was to investigate the effects of a 120 km desert running race (5 stages over 4 days) on the main physiologic parameters related to the individual aerobic work capacity. Incremental treadmill tests were carried out on 7 recreational long-distance runners (age: 50.4±11.8 years; body mass: 76.0±8.5 kg; mean±SD) before and 3-5 days after the competition. Maximal oxygen consumption (V O 2max ), ventilatory threshold and heart rate were obtained by standard methods; the mean energy cost of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The data reported in Table 4 as well as those originally obtained by Fusi et al (16) show that, in all subjects, the values (16). In addition, the average of the three individual values (A, B, C) in all six subjects of the present study was not significantly different than the corresponding average as obtained from the standard protocol over the four investigated speeds.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The data reported in Table 4 as well as those originally obtained by Fusi et al (16) show that, in all subjects, the values (16). In addition, the average of the three individual values (A, B, C) in all six subjects of the present study was not significantly different than the corresponding average as obtained from the standard protocol over the four investigated speeds.…”
Section: Discussionsupporting
confidence: 73%
“…At variance with these data, in our previous study we observed that the Cr values obtained from 0-to 10-s time window were significantly, albeit slightly, larger than those obtained in the 20to 30-s time window. Indeed, the average ratios of the slopes A/C and B/C amounted to 1.090 (range 1.067 to 1.119) and to 1.020 (range 1.000 to 1.056) before and to A/C ϭ 1.078 (range 1.000 to 1.116) and B/C ϭ 1.034 (range 0.975 to 1.103) after the desert race (16).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, a study reported a ~13% increase in Cr after a 65-km mountain ultra-marathon (Vernillo et al, 2015b ), whereas Gimenez et al ( 2013 ) observed only a ~5% increase until the 8th h before level-Cr plateaued and remained fairly constant during a 24-h treadmill run. By contrast, other experiments showed no change (Fusi et al, 2005 ; Schena et al, 2014 ; Vernillo et al, 2014 , 2015b ; Balducci et al, 2017 ). Further, Vernillo et al ( 2014 ) observed that Cr measured during uphill running decreased by ~14% after 330 km with a cumulative elevation gain of +24,000 m. The same authors confirmed and extended the previous observation (Vernillo et al, 2016 ), describing a ~7% decrease in Cr during different uphill running conditions after the same race.…”
Section: The Role Of Re In the Ultra-marathonmentioning
confidence: 83%
“…With this approach, referred to as O 2 cost, a series of independent studies have reported increments by up to 18% after ultra-marathons lasting 60 to 53 km·day −1 for 161 days (Millet et al, 2009 ; Lazzer et al, 2012 , 2015 ; Schena et al, 2014 ) (Figure 1 , top panel). Surprisingly, not all the studies reported such increases (i.e., deteriorations) (Millet et al, 2000 ; Fusi et al, 2005 ; Lazzer et al, 2014 ).…”
Section: The Role Of Re In the Ultra-marathonmentioning
confidence: 98%